Effect of some treatments on emission of volatile organic compounds (VOC) from chips used in pellets making processes. (3rd June 2015) - Gabriel, M.; Paczkowski, S.; Nicke, S.; Schütz, S.; Behn, C.; Kraft, R.; Roffael, E.
Abstract : Emission of volatile organic compounds (VOC) from wood during processing to pellets – significance of wood extractives. Cellulose, hemicelluloses and lignin are the main components of the cell wall in wood. Moreover, wood contains different amounts of extractives, depending on the wood species. Extractives in softwoods play an important role during processing of wood to different wood products. This work studies the influence of storage on the change of extractives as well as on the emission of monoterpenes (primary emission) and aliphatic aldehydes, as degradation products of fats and fatty acids (secondary emission). In case of pine wood storage for 2 days at 80°C proved to be more efficient in the reduction of emissions of terpenes and aldehydes than 4 weeks at 40°C. Quantitative differences between pine ( Pinus sylvestris ) and spruce ( Picea abies ) wood chips in the emission were evaluated and discussed. Pinewood emits about 10 times higher amounts of terpenes and aldehydes than spruce wood. The results indicate that the intense of change in primary and secondary emissions due to storage depends on the wood species as well as on the boundary conditions under which storage is carried out. In general, storage at high temperature (80°C) is much more effective than at low temperature (40°C). The results also reveal that removal of wood extractives from pine wood by extraction with ethanol-cyclohexane or treatment with sodium hydroxide decreases the emission of primary and secondary volatile organic compounds drastically. Nevertheless, after such treatments minute amounts of volatile organic compounds are still detectable.